2012
DOI: 10.1063/1.4719713
|View full text |Cite
|
Sign up to set email alerts
|

Feedback control of an azimuthal oscillation in the E × B discharge of Hall thrusters

Abstract: Feedback control of a low-frequency azimuthal wave known as a "rotating spoke" in the ExB discharge of a cylindrical Hall thruster was demonstrated. The rotating spoke is an m=1 azimuthal variation in density, electron temperature, and potential that rotates at about 10% of the local E × B electron rotation speed. It causes increased electron transport across the magnetic field and is suspected to be an ionization wave. Feedback control of this wave required special consideration because, although it causes a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…The carried out experiments showed that the boundary feedback system reduced amplitudes of both low-frequency and high-frequency oscillations in the Hall thruster. Currently, the interest to a suppression of the plasma instabilities in Hall thrusters by boundary feedback system is renewed [8].…”
Section: Application Of Feedback System For Suppression Of Instabmentioning
confidence: 99%
See 2 more Smart Citations
“…The carried out experiments showed that the boundary feedback system reduced amplitudes of both low-frequency and high-frequency oscillations in the Hall thruster. Currently, the interest to a suppression of the plasma instabilities in Hall thrusters by boundary feedback system is renewed [8].…”
Section: Application Of Feedback System For Suppression Of Instabmentioning
confidence: 99%
“…The first of them is in intervals {0, d 1 } and {d 1 , d 2 }, respectively. The second necessary condition, we obtain integrating(8) over an infinitely small interval around the point d 1 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few years a significant number of experiments [2][3][4][5][6][7] have been carried out to detect the presence of the spoke and evaluate the influence of this oscillation on the electron mobility. Those experiments make use of high-speed imagery to detect the spoke travelling in the azimuthal direction and a segmented anode in the back of the channel to measure the electron current as a function of the azimuthal coordinate and time.…”
Section: A Experimental Results For Low Frequency Oscillationsmentioning
confidence: 99%
“…5−8 While these disturbances have received much attention for their possible influence on Hall thruster operation, efficiency, and plume divergence, the underlying physical causes of these phenomena have not been fully understood. 8,9 Extensive experimental campaigns using an annular thruster have been undertaken to characterize the propagation of the instabilities, as well as the various mode transitions that arise from adjustment of the operating parameters. 10,11 Increased background pressure levels have also been found to suppress breathing and spoke oscillations.…”
Section: Introductionmentioning
confidence: 99%